The Correlation Between Students’ Perception on Merdeka Curriculum and Their Motivation - Gustiani, Tia; Kardena, Absharini (International Journal of English Education and Linguistics (IJoEEL), 2024)
Curriculum plays an important role in education, including English education. On the other side, motivation is also important for the students when learning English. During the implementation of the Merdeka curriculum, there were many obstacles that made students less motivated to learn. This research aims to figure out the correlation between students’ perceptions of the Merdeka curriculum and their motivation to learn English. The findings of this research revealed that the correlation coefficient between the two variables was 0.193. It means that there was a very low positive correlation between the students’ perception of the Merdeka curriculum and their motivation to learn English. The perception of the students could be influenced by several factors, such as how a person articulates their understanding of the subject. On the other side, motivation is also influenced by several factors, such as individual needs and desires (the input dimension), the expertise and demeanor of teachers, and the obstacles teachers encounter in school-based assessments (the process dimension).